2021
DOI: 10.1177/09697330211005103
|View full text |Cite
|
Sign up to set email alerts
|

Tertiary hospital nurses’ ethical sensitivity and its influencing factors: A cross-sectional study

Abstract: Background: High ethical sensitivity positively affects the quality of nursing care; nevertheless, Chinese nurses’ ethical sensitivity and the factors influencing it have not been described. Research objectives: The purpose of this study was to describe ethical sensitivity and to explore factors influencing it among Chinese-registered nurses, to help nursing administrators improve nurses’ ethical sensitivity, build harmony between nurses and patients, and promote the patients’ health. Research design: This was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…The average moral sensitivity score of this study was similar to the average moral sensitivity score (40.22 ± 7.08) of general nurses in Hunan Province hospitals [37,40]. The medium level of moral sensitivity of ICU nurses is consistent with other research results [10,41].…”
Section: Discussionsupporting
confidence: 89%
“…The average moral sensitivity score of this study was similar to the average moral sensitivity score (40.22 ± 7.08) of general nurses in Hunan Province hospitals [37,40]. The medium level of moral sensitivity of ICU nurses is consistent with other research results [10,41].…”
Section: Discussionsupporting
confidence: 89%
“…By acquiring knowledge, clinical nurses can provide patients with effective preventive care. 17 The results of this study revealed that the scoring rate for the PI prevention behaviour dimension among paediatric ICU nurses was only 71.31%, indicating a low rate of implementation of PI prevention among paediatric ICU nurses. This is related to the lack of guidelines and consensus on PI prevention in paediatrics and the lack of evidence‐based prevention strategies, in addition, the lack of awareness of prevention among nurses.…”
Section: Discussionmentioning
confidence: 69%
“…The change of preventive behaviour towards PI is predicated on the retention of pertinent theoretical knowledge among nurses. By acquiring knowledge, clinical nurses can provide patients with effective preventive care 17 . The results of this study revealed that the scoring rate for the PI prevention behaviour dimension among paediatric ICU nurses was only 71.31%, indicating a low rate of implementation of PI prevention among paediatric ICU nurses.…”
Section: Discussionmentioning
confidence: 72%
“…A moral burden is accompanied by anguish or moral suffering that can interfere with the quality of care [45]. Prior research has shown an inverse relationship between moral suffering and the ethical climate, implying that a more positive ethical climate results in lower moral suffering and increased job satisfaction [22,46].…”
Section: Discussionmentioning
confidence: 99%